Nanoparticle applications in agriculture: overview and response of plant-associated microorganisms - Mgadi, Katiso; Ndaba, Busiswa; Roopnarain, Ashira; Rama, Haripriya; Adeleke, Rasheed (Frontiers in Microbiology, 2024)
Globally, food security has become a critical concern due to the rise in human population and the current climate change crisis. Usage of conventional agrochemicals to maximize crop yields has resulted in the degradation of fertile soil, environmental pollution as well as human and agroecosystem health risks. Nanotechnology in agriculture is a fast-emerging and new area of research explored to improve crop productivity and nutrient-use efficiency using nano-sized agrochemicals at lower doses than conventional agrochemicals. Nanoparticles in agriculture are applied as nanofertilizers and/or nanopesticides. Positive results have been observed in terms of plant growth when using nano-based agricultural amendments. However, their continuous application may have adverse effects on plant-associated rhizospheric and endospheric microorganisms which often play a crucial role in plant growth, nutrient uptake, and disease prevention. While research shows that the application of nanoparticles has the potential to improve plant growth and yield, their effect on the diversity and function of plant-associated microorganisms remains under-explored. This review provides an overview of plant-associated microorganisms and their functions. Additionally, it highlights the response of plant-associated microorganisms to nanoparticle application and provides insight into areas of research required to promote sustainable and precision agricultural practices that incorporate nanofertilizers and nanopesticides.